2022
DOI: 10.1002/poc.4322
|View full text |Cite
|
Sign up to set email alerts
|

The effect of zero‐point energy in simulating organic reactions with post‐transition state bifurcation

Abstract: Ambimodal reactions involve a single transition state leading to multiple products. To assess the ratio of the bifurcation products, quasiclassical trajectories (QCTs) are initiated from transition state geometries that are randomly sampled using the zero‐point energy (ZPE) plus thermal energy of a molecule's vibrational modes. However, in the QCTs, the influence of ZPE percentage in the resulting bifurcation ratio and time gap between formation of bonds is not well understood. To benchmark the effect of varyi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Recently, Tremblay et al have also shown that the ZPE percentage affects the bifurcation ratio. 78 The HCO + + H 2 O fragments for RPMD are slightly less than those for classical MD, but both tendencies are similar. One possible reason of the slight difference at high temperature could be the procedure for solving the EOMs.…”
Section: Resultsmentioning
confidence: 93%
“…Recently, Tremblay et al have also shown that the ZPE percentage affects the bifurcation ratio. 78 The HCO + + H 2 O fragments for RPMD are slightly less than those for classical MD, but both tendencies are similar. One possible reason of the slight difference at high temperature could be the procedure for solving the EOMs.…”
Section: Resultsmentioning
confidence: 93%
“…13 Previously, the reaction system was investigated using the QCT method but at the B3LYP/6-31G(d) level. 12 Here, we investigated this reaction at the GFN2-xTB level, and a schematic of the PES is shown in Figure 1B. The PES properties obtained from the GFN2-xTB calculations were compared with those obtained from the B3LYP and M06 DFT calculations in Figure S1b.…”
Section: Intramolecular Cycloaddition Between Dienes and Trienesmentioning
confidence: 99%
“…In this study, we investigated three PTSB systems, namely, the Diels-Alder (DA) cycloaddition of cyclopentadiene and nitroalkene, 11 intramolecular cycloaddition between a diene and triene, 12,13 and DA cycloaddition involving proton transfer, 14 and discussed the bifurcation dynamics properties with the initial vibrational features at the ambimodal TS. Previous theoretical studies demonstrated the PTSB properties of PESs in these reactions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…And is it sufficient merely to determine which branch of the bifurcation is initially selected in order to answer that question? By focusing on the symmetrical case, one can be certain that any answers highlight features of the dynamics that are not influenced by differences in gradient leading to the two products, as there would be in all unsymmetrical cases. …”
Section: Introductionmentioning
confidence: 99%